Spatial fiscal interactions in Colombian municipalities: Evidence from oil price shocks - Raju Mainali (Journal of Risk and Financial Management, 2021)
This study provides an empirical investigation of fiscal interactions in the context of a developing country. I examine three fiscal components - budget balance, tax revenue, and public spending - to measure spatial interactions between Colombian municipalities from 2000 to 2010. I am using variables on municipalities' general characteristics, fiscal variables, and variables related to the conflict. I use a quasi-experimental identification strategy exploiting exogenous variation from global oil price shocks that affect Colombian municipalities to different degrees depending on local oil endowments. I find significant spatial interaction in taxes but no significant interaction concerning budget balance and total public spending. This suggests that even though there is local tax competition, municipalities do not mimic their neighbors to decide whether to offset tax changes by changes in borrowing or spending.
Keywords: H71; H72; O18; O23; R5; 330; budget balance competition; expenditure competition; fiscal interaction; spatial interaction quasi-experimental; tax competition